Monetary and macroprudential policies in the presence of external shocks: evidence from an emerging economy - Lubis, Alexander; Alexiou, Constantinos; Nellis, Joseph G. (Emerald, 2021)
Purpose This paper examines the impact of using the reserve requirements, combined with foreign exchange (FX) intervention, as key instruments in an inflation-targeting framework. Design/methodology/approach In the context of a dynamic stochastic general equilibrium (DSGE) framework and using Bayesian techniques, the authors estimate a model for the Indonesian economy using quarterly data spanning the period 2005Q2–2019Q4. Findings The reserve requirement is found to assume a complementary role to that of the interest rate policy and FX intervention when used to stabilise the macroeconomy. Originality/value This paper provides a benchmark for other emerging countries that consider adopting the inflation targeting framework and impose an FX intervention as part of their monetary policy.
Keywords: DSGE; Reserve requirement; Foreign exchange intervention; Macroprudential policy; Monetary policy